Serotyping and the Dienes reaction on Proteus mirabilis from hospital infections - de Louvois, J. (1969)
The serotype of 320 strains of Proteus mirabilis from clinical material was determined. Using 20 O antisera and four H antisera 61% of strains could be fully identified and 90% partially identified. A large number of serotypes were recognized but no difference was found between the serotype of organisms infecting the urinary tract and those from other infections. Biochemically identical organisms found in the same ward generally differed in serology. Proteus mirabilis was isolated from the faeces of 84·5% of 84 patients with urinary infection and from none of 20 normal controls. By serology and the Dienes test 61% of the organisms isolated from the urine and faeces of a single patient were identical, indicating that infection arose from the intestine. Most groups of serologically identical strains could, by the Dienes test, be further divided into a number of subtypes indicating that the strains were different and that cross infection had not been responsible for their spread. With three serological groups, however, the majority of strains belonged to a single Dienes type and it was concluded that these organisms had been spread from a common reservoir or carrier. Because of the unreliability of the Dienes test when carried out on random organisms it is suggested that reliable results can only be obtained by combining the Dienes test with serotyping.